Description of Sculptured Symbol Stone at Rayne and Small Cross at Culsalmond, Aberdeenshire (Proceedings of the Society of Antiquaries of Scotland, 1916)
The symbols inscribed on the Rayne stone are the Mirror Case, the Double Crescent, and a Rectangle with rod attached, of which no previous example has been found on any of the Scottish sculptured stones. The diorite stone at Culsalmond has a small plain incised cross formed of two lines crossing each other at right angles near the centre.